WOOD-BASED BUILDING MATERIALS WITH A THERMAL ENERGY STORAGE FUNCTION - Nazari, Meysam; Jebrane, Mohamed; Terziev, Nasko (Innovation in Woodworking Industry and Engineering design, 2025)
Encapsulating of phase change materials (PCM) in ceilings, floors and walls improved energy storage in buildings. The results show 10% saving of thermal energy by using bio-based, building materials with added functionality. The environmental impact of fossil-based materials on the construction industry and significant energy consumption in housing have driven the production of bio-based, renewable and sustainable materials for building applications. This is achieved by incorporating bio-based PCM into wood materials for thermal energy storage in residential buildings. Phase change materials absorb and release heat when changing from a solid to a liquid state. Organic PCM in form of fatty acids or esters produced from renewable resources, e.g., vegetable oils are suitable for the purpose. PCM can be impregnated in solid wood, wood fibers or sawdust and in the developed wood-based composite materials. The bio-composites store and release heat energy in the human comfort temperature range of 18–21°C. A step in the technology is the development of a bio-composite consisting of sawdust impregnated with ethyl palmitate (EP) as PCM and linseed oil as bio-based binder. The composite consists of 25% ester and has 50 J/g latent heat while being thermally stable up to 200°C. The new building materials are exposed in models for long-term monitoring and data collection for material behaviour and LCA. The thermal energy saving after 1 year of exposure was 10% and the model house had a better climate performance with 5.4% lower impact during its lifetime in comparison to the model house without PCM.